FARMERS’ AWARENESS AND ITS DETERMINANTS OF DIGITAL TECHNOLOGIES IN AGRICULTURE-EVIDENCE FROM RURAL TELANGANA - P. RADHIKA and A. MEENA, P. ASHWINI, ALDAS JANAIAH, G. P. SUNANDINI (The Journal of Research, PJTSAU, 2023)
Digital technologies in agriculture are expected to play an important role in dissemination of new knowledge timely and quickly, as well as in providing solution to growing labour shortage in agriculture. This study was carried out in three districts representing three agricultural zones in Telangana state to assess farmers’ level of awareness about digital technologies inagriculture. A sample of 180 farmers, 90 from progressive regions and another 90 from backward regions in selected districts were interviewed during the year 2020-21 using a pre structured schedule. Farmers’ responses (Yes or No) to a set of twelve questions were elicited to assess farmers’ awareness of five selected digital technologies. Farmers’ Digital Awareness Index (FDAI) was developed using farmers’ responses and its determinants were examined through a multiple linear regression analysis. Results indicated that average FDAI in progressive regions was comparatively higher than backward regions. Nearly two third of sample farmers have the FDAI of 40 per cent and above. FDAI was positively and significantly associated with education and farm size, while age was negatively associated.